2009
DOI: 10.1093/jac/dkp463
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and epidemiology of levofloxacin resistance in Streptococcus pneumoniae: experience from a tertiary referral hospital in England

Abstract: ), isolates of S. pneumoniae cultured by the LTHTR microbiology laboratory were examined by Etest to determine MICs of levofloxacin. Isolates from patients in whom there was a shift towards colonization with S. pneumoniae of reduced levofloxacin susceptibility were further characterized by serotyping, multilocus sequence typing (MLST) and sequencing of parC and gyrA genes.Results: Eight hundred and sixty-five isolates were collected; however, 772 isolates from 652 patients were recoverable; 412 (53.4%) came fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Levofloxacin is a broad-spectrum fluoroquinolone with greater antimicrobial activity against S. pneumoniae than older fluoroquinolones. However, increased use of fluoroquinolones has allowed for increasing emergence of levofloxacin-resistant pneumococci [ 41 , 42 ]. Kang et al [ 43 ] recently reported that approximately 4.7 % of pneumococcal isolates collected from individuals affected with community-acquired pneumonia in Asian countries were levofloxacin-nonsusceptible, and that independent risk factors for levofloxacin-nonsusceptible pneumococcal pneumonia were prior treatment with fluoroquinolones, cerebrovascular disease, and healthcare-associated infections.…”
Section: Resultsmentioning
confidence: 99%
“…Levofloxacin is a broad-spectrum fluoroquinolone with greater antimicrobial activity against S. pneumoniae than older fluoroquinolones. However, increased use of fluoroquinolones has allowed for increasing emergence of levofloxacin-resistant pneumococci [ 41 , 42 ]. Kang et al [ 43 ] recently reported that approximately 4.7 % of pneumococcal isolates collected from individuals affected with community-acquired pneumonia in Asian countries were levofloxacin-nonsusceptible, and that independent risk factors for levofloxacin-nonsusceptible pneumococcal pneumonia were prior treatment with fluoroquinolones, cerebrovascular disease, and healthcare-associated infections.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the question cannot be answered if resistance may have developed during therapy resulting in clinical failure. This question was recently addressed by Orr et al [205] who investigated in a tertiary referral hospital in England in 865 patients the incidence and epidemiology of levofloxacin-resistant pneumococci. In six patients a shift towards reduced levofloxacin-susceptibility or -resistance was recorded.…”
Section: Fluoroquinolone Resistance Epidemiologymentioning
confidence: 99%
“…In six patients a shift towards reduced levofloxacin-susceptibility or -resistance was recorded. Five patients had acquired a new distinct strain and one patient only harboured the same clone [205]. This study revealed that levofloxacin pneumococcal resistance still is uncommon and that in vivo fluoroquinolone resistance development is very rare.…”
Section: Fluoroquinolone Resistance Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation